(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
هدفت الدراسة إلى المقارنة بين الطريقة الخطية والطريقة المئينية لمعادلة درجات صورتي اختبار تحصيلي في مادة الرياضيات للصف الرابع الأساسي، وذلك بالاعتماد على معيار الخطأ المعياري للمعادلة، ولتحقيق ذلك استخدم المنهج الوصفي التحليلي، وأعدت صورتين ذي الاختيار من متعدد وتألفت كل صورة من (24) سؤالاً، حيث جرى التحقق من صدقهما وثباتهما. تكونت العينة من (1150) تلميذاً وتلميذةً من تلاميذ الصف الرابع الأساسي في محافظة دمشق. أظهرت النتائج أنّ الطريقة الخطية أكثر فاعلية من الطريقة المئينية عند استخدام تصميم المجموعة الواحدة في المعادلة الأفقية، واقترح استخدام الطريقة الخطية لمعادلة درجات صور الاختبار التحصيلي في مادة الرياضيات للصف الرابع. The purpose of this study is to compare between linear and equipercentile methods for equating two forms of achievement test in mathematics for the fourth elementary class, based on the standard error of equating criterion. For that, the researcher used the descriptive analytical approach, and prepared two reliable valid forms of achievement test using multiple-choice. Each form consists of (24) items. The research sample consists of (1150) pupils of the fourth elementary class in Damascus. The results showed that the linear method is more efficient than the equipercentile method when the horizontal equating undertook a single group. The researcher suggested using the linear method for equating two forms of achievement test in mathematics for the fourth elementary class.